1995
DOI: 10.1074/jbc.270.20.11845
|View full text |Cite
|
Sign up to set email alerts
|

Properties of and Proteins Associated with the Extracellular ATPase of Chicken Gizzard Smooth Muscle

Abstract: The chicken gizzard smooth muscle extracellular ATPase (ecto-ATPase) is a low abundance, high specific activity, divalent cation-dependent, nonspecific nucleotide triphosphatase (NTPase). The ATPase is a 66-kDa glycoprotein with a protein core of 53 kDa (Stout, J.G. and Kirley, T.L. (1994) J. Biochem. Biophys. Methods 29, 61-75). In this study we evaluated the characteristics of a bank of monoclonal antibodies raised against a partially purified chicken gizzard ecto-ATPase. 18 monoclonal antibodies identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
7
44
2
Order By: Relevance
“…Thus, binding of ATP appears to be sufficient to cause protection against trypsin digestion whereas mutation of the whole Walker A motif is required to decrease ATP binding and hydrolysis. ecto-kinase substrate concentration (33), (iii) involvement in signal transduction (2,25,27), and (iv) involvement in cellular adhesion (17,20,42). So far the physiological role of OppA in Mycoplasma hominis remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, binding of ATP appears to be sufficient to cause protection against trypsin digestion whereas mutation of the whole Walker A motif is required to decrease ATP binding and hydrolysis. ecto-kinase substrate concentration (33), (iii) involvement in signal transduction (2,25,27), and (iv) involvement in cellular adhesion (17,20,42). So far the physiological role of OppA in Mycoplasma hominis remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Ecto-nucleotidases have now been characterized from a diversity of tissues and species, ranging from insects to parasites to plants and to mammals (6,10,24,25). Substrate specificity of ATPDases varies broadly as individual systems are studied.…”
Section: Discussionmentioning
confidence: 99%
“…We are interested in determining structural and functional similarities and differences between the ecto-ATPases (which do not hydrolyze nucleoside diphosphates) and ecto-apyrases (ectoATPDases), which hydrolyze nucleoside diphosphates at similar rates as nucleoside triphosphates. Previously (17,18), we purified and characterized the ecto-ATPase from chicken smooth muscle (gizzard). In addition, we showed that chicken stomach was a good source of ecto-ATPDase (19) that was immunologically indistinguishable from that purified by others from chicken oviduct and liver (20).…”
mentioning
confidence: 99%